PENGARUH BAP DAN NAA TERHADAP INDUKSI KALUS DAN KANDUNGAN ARTEMISININ DARI Artemisia annua L. - Purnamaningsih, Ragapadmi; Ashrina, Misky (BERITA BIOLOGI, 2011)
Malaria is a global health problem that threatens 300-500 million people and kills more than one million people annually.Artemisinin, a sesquiterpen secondary plant metabolite extracted from Artemisia annua L., is a promising and potent antimalarial drug which has a remarkable activity against chloroquine resistant to Plasmodium falciparum. To counter the present low content(0.01-0.5%) of artemisinin in A. annua L.is a limitation to commercial production of the drug and uneconomical chemical synthesis. A research was conducted to induce callus production by using Murashige-Skoog (MS) medium added with NAA (0, 0.5 and 1 mg/1) and BAP (0, 0.5 dan 1 mg/1) and also to produce artemisinin from the calli. Complete Randomized Design was used in the research. Callus cultures were induced from leaf explants of A. annua. The research reports succesful approach for production of artemisinin by callus cultures of A. Annua. Medium formulation of MS basal media added with plant growth regulators BAP 0.5 mg/1 and NAA 0.5 mg/1 give the best result for callus induction than others, with callus fresh weight 844,4 mg, artemisinin content 0.73%, dry weight 216.6 mg and total weight of artemisinin 1.58 mg.